Langerhans cell histiocytosis in children with congenital anomalies: A population‐based record linkage study. Issue 2 (24th February 2015) - Salotti, Jane A.; Tennant, Peter W.G.; Windebank, Kevin; Rankin, Judith
Abstract : Background: The etiology of Langerhans cell histiocytosis (LCH), a rare cancer‐like disorder of the immune system, is largely unknown although a genetic component has been suggested based on familial cases, and reports of chromosome instability and genetic mutation. Associations between various cancers and congenital anomalies have been reported and although congenital anomalies have been noted in children with LCH only one study to date has reported their frequency. An association between congenital anomalies and LCH may suggest a common etiological pathway, in particular, a genetic pathway. Methods: Data from two coterminous registries in the same geographic region were used. All cases of LCH on the Northern Region Young Persons Malignant Disease Register diagnosed between 1985 and 2010 were cross‐matched with live‐born cases of congenital anomaly registered by the Northern Congenital Abnormality Survey. Results: A total of 819, 890 children and young people were born during 1985 to 2008. Of these, 13, 799 (1.7%) had a congenital anomaly and 39 (0.005%) were diagnosed with LCH. Three LCH cases were identified among those with congenital anomalies, all three of whom had congenital heart disease. The relative risk of LCH for those with a congenital anomaly, compared with those without, was 4.87 (95% confidence interval, 1.50–15.81; p = 0.03). Conclusion: LCH was associated with congenital anomaly in a small but statistically significant number of patients, raising the possibility of a common genetic pathway in some cases. Birth Defects Research (Part A), 2015 . © 2015 Wiley Periodicals, Inc. Birth Defects Research (Part A) 103:157–160, 2015 © 2015 Wiley Periodicals, Inc.